Relations of Pre-Onset Cannabis, Alcohol, and Tobacco Use with the Age at Onset of Prodrome and Age at Onset of Psychosis in First-Episode Patients - Compton, Michael T. (2009)
OBJECTIVE: Several reports suggest that cannabis use is associated with an earlier age at onset of psychosis, though not all studies have operationalized cannabis use as occurring prior to onset of symptoms. This study addressed whether pre-onset cannabis use (and alcohol and tobacco use) is associated with an earlier age at onset of prodromal and psychotic symptoms. Additionally, effects of the progression of frequency of use were examined through time-dependent covariates in survival analyses. METHOD: First-episode patients (n=109) hospitalized in two public-sector inpatient psychiatric units underwent in-depth cross-sectional/retrospective assessments. Prior substance use and ages at onset of prodromal and psychotic symptoms were determined using standardized methods. Cox regression modeling was conducted. RESULTS: Whereas classifying participants according to maximum frequency of use prior to onset (none, ever, weekly, or daily) revealed no significant effects of cannabis or tobacco use on risk of onset, analysis of change in frequency of use prior to onset indicated that progression to daily cannabis and tobacco use was associated with increased risk of onset of psychotic symptoms. Similar or even stronger effects were observed when onset of illness/prodromal symptoms was the outcome. A gender by daily cannabis use interaction was observed—progression to daily use resulted in a much larger increased relative risk of onset of psychosis in females than males. CONCLUSIONS: Pre-onset cannabis use may hasten the onset of psychotic as well as prodromal symptoms. Age at onset is a key prognostic factor in schizophrenia, and discovering modifiable predictors of age at onset is crucial.